La place de l’autoévaluation dans l’enseignement de l’écrit - Barkat, Amel (Journal of Human Sciences, 2018)
Selfevaluation, one of the new practices used in the teaching programmes since the last reform of the algerian educational system. This practice targets the regulation of the content taught according to the informations that the learners provide us about their learning. In this contribution, we aim at knowing the position of the selfevaluation in the class practices of our teachers. More precisely, we are trying to focus on the teachers’ use of the selfevaluation grills found in the textbook during a written production activity.